Invariants of GLn(𝔽q) in polynomials modulo Frobenius powers. Issue 4 (5th July 2017) - Lewis, J.; Reiner, V.; Stanton, D.
Abstract : Conjectures are given for Hilbert series related to polynomial invariants of finite general linear groups: one for invariants mod Frobenius powers of the irrelevant ideal and one for cofixed spaces of polynomials.